2012
DOI: 10.1016/j.chemosphere.2012.01.032
|View full text |Cite
|
Sign up to set email alerts
|

Study on the initial velocity distribution of exhaled air from coughing and speaking

Abstract: Increasing concerns about the spread of airborne pathogens such as severe acute respiratory syndrome (SARS) and novel swine-origin influenza A (H1N1) have attracted public attention to bioaerosols and protection against them. The airborne pathogens are likely to be expelled from coughing or speaking, so the physical data of the exhaled particles plays a key role in analyzing the pathway of airborne viruses. The objective of this study was to analyze the initial velocity and the angle of the exhaled airflow fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
154
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 172 publications
(166 citation statements)
references
References 19 publications
10
154
2
Order By: Relevance
“…The mouth opening area was almost constant during the cough period, at about 4±0.95 cm 2 for males and 3.37±1.4 cm 2 for females [29]. A recent study by Kwon et al [30] showed that the average coughing velocity is 15.3 m/s for males, and 10.6 m/s for females.…”
Section: Assumptions In the Calculationsmentioning
confidence: 95%
See 1 more Smart Citation
“…The mouth opening area was almost constant during the cough period, at about 4±0.95 cm 2 for males and 3.37±1.4 cm 2 for females [29]. A recent study by Kwon et al [30] showed that the average coughing velocity is 15.3 m/s for males, and 10.6 m/s for females.…”
Section: Assumptions In the Calculationsmentioning
confidence: 95%
“…The airflow in buildings is designed to be less than 0.25 m/s for thermal comfort [28]. The jet speed of coughing and breathing can be 6e22 m/s (over 10 m/s on average) and 1e5 m/s respectively [13,29,30]. The transport of the expiratory droplets can be considered as two stages, with the primary being coughing/exhalation jet transport, followed by the secondary, dispersion by room airflow.…”
Section: Introductionmentioning
confidence: 99%
“…A maximum velocity range of 6–28 m/s has been detected, and the cough was found to expand linearly in the initial stage [6, 7, 1113]. Tang [14] estimated the maximum velocity to be 8 m/s using the Schlieren imaging technique.…”
Section: Introductionmentioning
confidence: 99%
“…The average expiration air velocity was 11.7m/s for coughing and 3.9m/s for speaking. Similarly, the initial velocity and angle of exhaled airflow from coughing and speaking was measured with 26 tested subjects using PIV by Kwon et al [68]. VanSciver et al [69] also applied PIV system to measure the velocity field of human cough from 29 subjects.…”
Section: Human Airflowsmentioning
confidence: 99%